2016
DOI: 10.1038/nm.4148
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose interleukin-2 treatment selectively modulates CD4+ T cell subsets in patients with systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a potentially life-threatening autoimmune disease characterized by altered balance of activity between effector and regulatory CD4(+) T cells. The homeostasis of CD4(+) T cell subsets is regulated by interleukin (IL)-2, and reduced production of IL-2 by T cells is observed in individuals with SLE. Here we report that treatment with low-dose recombinant human IL-2 selectively modulated the abundance of regulatory T (Treg) cells, follicular helper T (TFH) cells and IL-17-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
389
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 482 publications
(422 citation statements)
references
References 28 publications
19
389
0
5
Order By: Relevance
“…Less grade II-IV aGVHD (if IL-2 discontinued early) [36] HCV vasculitis 1-3 × 10 6 IU/m 2 /day from days 1 to 5 every 21 days, 4 courses 90% Clinical response [40] Systemic lupus erythematosus 1 × 10 6 IU/m 2 /day every other day for 14 days, 3-6 courses 95% Clinical response [43] Alopecia areata 1-3 × 10 6 IU/m 2 /day from days 1 to 5 every 21 days, 4 courses 80% Clinical response [42] Type1-diabetus 0.3-3 × 10 6 IU/m 2 /day, daily administration for 5 days Selective Treg increase [41] 1 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less grade II-IV aGVHD (if IL-2 discontinued early) [36] HCV vasculitis 1-3 × 10 6 IU/m 2 /day from days 1 to 5 every 21 days, 4 courses 90% Clinical response [40] Systemic lupus erythematosus 1 × 10 6 IU/m 2 /day every other day for 14 days, 3-6 courses 95% Clinical response [43] Alopecia areata 1-3 × 10 6 IU/m 2 /day from days 1 to 5 every 21 days, 4 courses 80% Clinical response [42] Type1-diabetus 0.3-3 × 10 6 IU/m 2 /day, daily administration for 5 days Selective Treg increase [41] 1 3…”
Section: Resultsmentioning
confidence: 99%
“…Considering the broad clinical relevance of this mechanism, the restoration of normal Treg homeostasis using low-dose IL-2 could be worth considering for the re-induction of tolerance in patients with autoimmunity as well as GVHD. So far, clinical trials for various autoimmune diseases have been performed and promising results were reported in some diseases including systemic lupus erythematosus (SLE) and type-1 diabetes, as shown in Table 1 [40][41][42][43][44]. Ongoing trials are recruiting patients with other autoimmune diseases such as rheumatoid arthritis, Crohn's disease, ulcerative colitis, and so on.…”
Section: Application For Autoimmune Diseasesmentioning
confidence: 99%
“…We started our study in 2013, with clinical responses as the primary end point and an emphasis on immuno logical responses, including changes in T FH , T H 17 and T reg cells, as secondary end points 9 . For the first time, we demonstrated that low-dose IL-2 therapy could suppress T FH and T H 17 cells in humans 1 . In addition, using a mouse model, we revealed that suppression of T FH and T H 17 cells was as sensitive to low-dose IL-2 as the promotion of T reg cells.…”
mentioning
confidence: 90%
“…We thank Dr Jens Y. Humrich and Dr Gabriela Riemekasten for their interest in our study 1 , which they discussed in a News & Views commentary (Humrich, J. Y. & Riemekasten, G. The rise of IL-2 therapy -a novel biologic treatment for SLE.…”
mentioning
confidence: 99%
See 1 more Smart Citation